2016
DOI: 10.1016/j.ajhg.2016.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that the 5p12 Variant rs10941679 Confers Susceptibility to Estrogen-Receptor-Positive Breast Cancer through FGF10 and MRPS30 Regulation

Abstract: Genome-wide association studies (GWASs) have revealed increased breast cancer risk associated with multiple genetic variants at 5p12. Here, we report the fine mapping of this locus using data from 104,660 subjects from 50 case-control studies in the Breast Cancer Association Consortium (BCAC). With data for 3,365 genotyped and imputed SNPs across a 1 Mb region (positions 44,394,495-45,364,167; NCBI build 37), we found evidence for at least three independent signals: the strongest signal, consisting of a single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 26 publications
(50 reference statements)
1
62
0
5
Order By: Relevance
“…Sequential conditional analysis was performed to clarify the independent effects among significant loci (P ≤ 1.00 × 10 −4 ), and conditional significance level was set at P ≤ 1.00 × 10 −3 for the overall lung cancer risk. 29,30 We used the linear regression model to evaluate the associations between identified SNPs and telomere length in peripheral blood leukocytes. All analyses were performed using plink 1.9 and R software (version 3.1.1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sequential conditional analysis was performed to clarify the independent effects among significant loci (P ≤ 1.00 × 10 −4 ), and conditional significance level was set at P ≤ 1.00 × 10 −3 for the overall lung cancer risk. 29,30 We used the linear regression model to evaluate the associations between identified SNPs and telomere length in peripheral blood leukocytes. All analyses were performed using plink 1.9 and R software (version 3.1.1).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the advances of ENCODE project and 1000 Genomes project, we defined TERT‐CLPTM1L region as chr5: 753 287 ∼ 1 753 287 (hg19, 500 kb upstream and downstream from TERT gene). Similar strategy was adopted by Dunning et al in their fine mapping study for breast cancer …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is unlikely, though possible, that these physiological differences are related to prognosis of ER+ breast cancer. CYP2D6 has very weak affinity for testosterone[41], suggesting a possible relationship with ER+ breast cancer occurrence or prognosis, however, associations of CYP2D6 polymorphisms with occurrence of ER+ breast cancer have not been detected in very large genome-wide screens[42]. …”
Section: Discussionmentioning
confidence: 99%
“…Rather than altering protein sequence, and consequently protein function or structure, it seems that most raSNPs, or those in linkage disequilibrium with them, may act in cis to regulate the expression levels of target genes located distally and proximally [3][4][5] . The biological effect of raSNPs has so far been detected by expression quantitative trait loci analysis (eQTL) 3,[6][7][8] , but also, though less frequently, through the analysis of differential allelic expression (DAE) 9,10 . A few functional studies for BC raSNPs have confirmed this cis-regulatory role, but have mainly focused on their potential to alter transcription factor binding sites 3,[6][7][8] .…”
Section: Introductionmentioning
confidence: 99%